SYAIR PENGANTIN BARU: Prophetic Literature Malay as a Deli - O.K. Sahril (Balai Bahasa Sumatera Utara, 2018)
Prophetic literature is a concept based on the prophetic work. Prioritize humanization, liberation, and transcendence. Prophetic literature is literature that is able to provide a balance between the social themes and spiritual themes, representing the history of humanity and prophetic values/religion. This paper uses qualitative survey methods. The theory used in this paper is a prophetic literary theory, which sees literature as a spiritual concepts and social concepts (habluminallah and habluminannas). This paper analyzed 107 text poem that became the subject of research. The findings of the research on text SPB, namely the alignment between the spiritual concept (habluminallah) and social concepts (habluminannas).